The Instrumental Role of Strategic Communication to Counter Industry Marketing Responses to Sugary Drink Taxes; Comment on "Understanding Marketing Responses to a Tax on Sugary Drinks: A Qualitative Interview Study in the United Kingdom, 2019" - Nandita Murukutla; Trish Cotter; Alexey Kotov (Kerman University of Medical Sciences, 2023)
Strong sugary drink taxes are effective at reducing sugary drinks consumption. In response, the sugary drinks industry employs various marketing strategies to undermine the taxes to protect and maintain its customer base. In their recent article in this journal, Forde et al present a framework for understanding how sugary drinks companies use marketing for this purpose. In this commentary, we reflect on this framework by drawing from recent experiences of sugary drinks industry marketing responses. Further, we review the global evidence on the instrumental role that strategic communication can play in protecting strong taxes from industry responses. We make a case for strategic communication as a vital tool in promoting and protecting sugary drinks tax proposals, both prior to and after their introduction.